2021
DOI: 10.3389/fnhum.2021.621620
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Alpha and Theta Oscillations Are Related to Complementary Aspects of Cognitive Control in Younger and Older Adults

Abstract: The resting-state human electroencephalogram (EEG) power spectrum is dominated by alpha (8–12 Hz) and theta (4–8 Hz) oscillations, and also includes non-oscillatory broadband activity inversely related to frequency (1/f activity). Gratton proposed that alpha and theta oscillations are both related to cognitive control function, though in a complementary manner. Alpha activity is hypothesized to facilitate the maintenance of representations, such as task sets in preparation for expected task conditions. In cont… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
39
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(63 citation statements)
references
References 75 publications
2
39
3
Order By: Relevance
“…Nonetheless, some alpha suppression should still occur when a new sound is presented. Of note, this prediction regarding stimulus-related alpha suppression occurs on top of the well-known general alpha reduction when the eyes open after being closed (e.g., Adrian and Matthews, 1934 ; Barry et al, 2007 ; Berger, 1929 ; Polich, 1997 ; Clements et al, 2021a ). Additionally, we hypothesize that it will be easier to generate and maintain new representations of auditory stimuli with closed than with open eyes because there will be little competition between vision and hearing, and that should be reflected in alpha dynamics.…”
Section: Introductionmentioning
confidence: 86%
See 3 more Smart Citations
“…Nonetheless, some alpha suppression should still occur when a new sound is presented. Of note, this prediction regarding stimulus-related alpha suppression occurs on top of the well-known general alpha reduction when the eyes open after being closed (e.g., Adrian and Matthews, 1934 ; Barry et al, 2007 ; Berger, 1929 ; Polich, 1997 ; Clements et al, 2021a ). Additionally, we hypothesize that it will be easier to generate and maintain new representations of auditory stimuli with closed than with open eyes because there will be little competition between vision and hearing, and that should be reflected in alpha dynamics.…”
Section: Introductionmentioning
confidence: 86%
“…Three blocks were resting-state: one with eyes open, one with eyes closed, and one with eyes open but wearing an eye-mask to block visual input. The resting state data were used for other purposes and are reported elsewhere ( Clements et al, 2021a ; Gyurkovics et al, 2021 ). The masked data were inconclusive 1 and 2 and are not described further.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, changes in the shape of 1/f activity in the brain have been linked to shifts in the balance between excitatory and inhibitory synaptic inputs in local neural circuits (Gao et al, 2017). Furthermore, although 1/f activity is often regarded as noise to be excluded before performing frequency-domain analyses (Gyurkovics et al, 2021), the shape parameters of 1/f activity have been found to be related to behavior and cognition (Bódizs et al, 2021;Clements, Bowie, et al, 2021;Immink et al, 2021;Lendner et al, 2020;Ouyang et al, 2020).…”
Section: Introductionmentioning
confidence: 99%